2009
DOI: 10.3727/096368909x484671
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Angina Cell Therapy (ReACT) Involving Autologous Bone Marrow Cells in Patients without Left Ventricular Dysfunction: A Possible Role for Monocytes

Abstract: Autologous bone marrow mononuclear cell (BMMC) transplantation has emerged as a potential therapeutic option for refractory angina patients. Previous studies have shown conflicting myocardium reperfusion results. The present study evaluated safety and efficacy of CellPraxis Refractory Angina Cell Therapy Protocol (ReACT), in which a specific BMMC formulation was administered as the sole therapy for these patients. The phase I/IIa noncontrolled, open label, clinical trial, involved eight patients with refractor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…Our earlier report also showed that in vitro growth of normal diploid cells was not inhibited by IFN activated monocytes [16]. These findings are also consistent with clinical trials in which low toxicity was seen in patients treated with autologous monocytes [48-50]. These observations imply that IFN activated monocyte may be relatively selective for tumor cells.…”
Section: Discussionsupporting
confidence: 83%
“…Our earlier report also showed that in vitro growth of normal diploid cells was not inhibited by IFN activated monocytes [16]. These findings are also consistent with clinical trials in which low toxicity was seen in patients treated with autologous monocytes [48-50]. These observations imply that IFN activated monocyte may be relatively selective for tumor cells.…”
Section: Discussionsupporting
confidence: 83%
“…Neither cell type integrated into the new blood vessels in the muscle, however, suggesting that the cells may be releasing angiogenic substances. The third study was a clinical trial in which patients with refractory angina received multiple injections of autologous bone marrow MNCs into viable, but ischemic myocardium (Hossne et al, 2009). Patients exhibited significant, progressive improvements in clinical angina classification that were maintained out to 18 months post-transplant as well as reduced ischemia as determined using stress technecium scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group revealed that surgical intramyocardial multiple one-time injections of autologous BM mononuclear cells in patients with refractory angina showed a progressive improvement in angina classification as well as in reperfused myocardium area during 18 month follow-up [ 96 ]. It is of interest that a positive correlation was noted between monocyte concentration in the graft formulation and clinical improvement ( Table 2 ).…”
Section: Monocytes Versus Stem Cells For Transplanmentioning
confidence: 99%